The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.4103/0971-6866.116116
|View full text |Cite
|
Sign up to set email alerts
|

Association between pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections disease and tumor necrosis factor-α gene−308 g/a, −850 c/t polymorphisms in 4-12-year-old children in Adana/Turkey

Abstract: OBJECTIVES:Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS) is a newly defined disease in neuropsychiatry and occurs with an autoimmune mechanism after Group A Beta Hemolytic Streptococcus (GABHS) infection. Tumor necrosis factor (TNF), encoded by TNF-α gene has an important role in the apoptotic mechanisms of autoimmune diseases. Recently, TNF-α polymorphisms and autoimmune/psychiatric disorders have been reported to be related. In this regard, we focused on to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(36 reference statements)
0
8
1
Order By: Relevance
“…This might have an indirect impact on behavior due to the reduced production of various metabolites involved in brain functions. Further, exon variants of the MBL gene and altered levels of TNF-α increase the susceptibility of PANDAS [67,68]. The treatment of PANDAS syndrome is still not obvious and specified, however, there are several alternatives that show promising results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might have an indirect impact on behavior due to the reduced production of various metabolites involved in brain functions. Further, exon variants of the MBL gene and altered levels of TNF-α increase the susceptibility of PANDAS [67,68]. The treatment of PANDAS syndrome is still not obvious and specified, however, there are several alternatives that show promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the MBL2 gene is suspected to be one of the diagnostic markers of PANDAS. According to Luleyap et al, TNF-α −308 AA polymorphism can be regarded as a molecular indicator of PANDAS [68]. Altered levels of TNF-α can be associated with exacerbation of PANDAS symptoms and facilitating autoimmune responses within the central nervous system.…”
Section: Genetic Approach To Ocd Including Pandasmentioning
confidence: 99%
“…To date, only a single, small molecular genetic study has been published for PANDAS, demonstrating a positive association between one genetic polymorphism (308 G/A – rs1800629) in the TNF- α promoter for PANDAS patients, using a hospital-based case-control study of 42 children with PANDAS and 58 healthy controls [66]. There was, however, no positive relationship between this 308 G/A polymorphism and anti-streptolysin O (ASO) titers, a serological indication of previous S. pyogenes infections.…”
Section: Genetic Risk Factors For Developing Sc or Pandasmentioning
confidence: 99%
“…In addition, a positron emission tomography (PET) imaging study found greater microglial activation in patients with PANDAS compared with controls (Kumar et al 2015). Another study found an association between the tumor necrosis factor (TNF)-a gene -308G/A polymorphism and patients with PANDAS (Luleyap et al 2013). A recent animal model designed to evaluate the relationship between nasopharyngeal infection and neuroinflammation showed that multiple intranasal infections with live GAS generate GAS-specific Th17 cells that migrate along olfactory sensory axons into the brain.…”
Section: Discussionmentioning
confidence: 99%